Pertanggungjawaban Organ Yayasan Terhadap Kewajiban Penyesuaian Badan Hukum Perspektif Kepastian Hukum - Hestianah, Hestianah; Suryahartati, Dwi; Amir, Diana (Magister Kenotariatan, Universitas Jambi, 2026)
This study was conducted to analyze the accountability of foundation organs to the obligation to adjust legal entities from the perspective of legal certainty. The formulation of the problem from this study is how to regulate the obligations of foundation organs to the adjustment of the foundation's legal entity, as well as how the accountability of foundation organs and the Ministry of Law and Human Rights to the adjustment of foundation legal entities from the perspective of legal certainty. The results of this study conclude that the legal regulation of the accountability of foundation organs is regulated in the Foundation Law and the Articles of Association of each foundation. The organs of the Foundation must carry out their duties well but there is still a need for advice, education and awareness of the management to develop and maximize the duties and obligations in managing the Foundatio.